The use Problem Based Learning Methods in Science Education - Muhammad Arsyad; Razia Khan; Chak Sothy (Journal Neosantara Hybrid Learning, 2024)
Science education plays a crucial role in developing students' critical thinking and problem-solving skills. However, traditional teaching methods often fail to engage students in meaningful learning experiences. To address this issue, Problem-Based Learning (PBL) has been introduced as an innovative instructional approach that encourages active learning and critical inquiry. This study aims to examine the effectiveness of the PBL method in science education by analyzing its impact on students' learning outcomes and engagement. This research employs a quasi-experimental design with two groups: an experimental group using the PBL method and a control group using conventional methods. Data were collected through pre-test and post-test assessments, student questionnaires, and classroom observations. The study involved secondary school students in a science subject. The findings reveal that students in the PBL group demonstrated higher academic achievement and improved problem-solving abilities compared to those in the control group. Additionally, PBL fosters greater student engagement, motivation, and collaboration during the learning process. In conclusion, the Problem-Based Learning method proves to be an effective strategy in science education, enhancing students' understanding and critical thinking skills. Educators are encouraged to implement PBL in science classrooms to create a more dynamic and interactive learning environment.